Intelligent autonomous drone - Loon, Zi Jian (Nanyang Technological University, 2023)
Drones are used in multiple industries such as military, construction, maritime and more. It has allowed many companies to work more efficiently while reducing the manpower labor and enhancing the worker’s safety at the same time. This technology has been constantly evolving and improving. Now, with the help of Artificial Intelligence (AI) algorithm, drones will be able to perform more automated tasks and be always adaptive to its environment which includes collision avoidance.